Takrifan-Takrifan Tentang Konsep Pembelajaran Merentasi Sejarah - Hamzah, Mohamad Daud (Penerbit Universiti Sains Malaysia, 1984)
This paper presents a historical survey of the interpretations of "learning". Around the eighteenth century the doctrine of "metal substance" formed the basis to view "learning" as an expansion of innate ideas either from within via self-unfoldrnent or from without via mental discipline. When this doctrine was replaced by the doctrine of mental state, "learning" was viewed as the establishment of associations among ideas acquired through experiences. In the late eighteenth century and also thoughout the nineteenth century both philosopher-psychologists and experimental psychologists interpreted "learning" as either the formation of associations among ideas or one of its abstractions in the forms of associations between situations and responses, and associations between stimuli and responses.